Síntese e análise dos quatro conceitos de análise linguística de Leonard Bloomfield (1887-1949): língua, fonema, falante e comunidade de fala - Rosa, Helda Núbia (2020)
Leonard Bloomfield (1887-1949) was an American professor, linguist and anthropologist. His works An Introduction to the Study of Language (1914) and Language (1933) are models of linguistics manuals, as Bloomfield intended to elaborate them in the perspective that they could serve as a source for future linguists, for this purpose, he compiled concepts of language scholars who researched on phonetics, phonemics, phonology, morphology and syntax. In addition to these two A set postulates of Language (1926) presents a series of axioms related to the aforementioned themes. Bloomfield went to great lengths to understand, select and organize the research carried out by comparators and neogrammarists, a work that began with the work of 1914 and concluded with the publication of 1933, which is why his works were exemplary with regard to the description of the language. In them, he tried to synthesize about the human being's interest in the study of language developed from the classical era until the 19th century, he tried to demonstrate how phonetics and phonemics are relevant to the understanding of the concepts pointed out in his works. From the comments of the speech community, Bloomfield was able to define, based on anthropology and psychology, the concept of phoneme, not without the help of all those who were concerned with defining the theme at that time. The linguists of the Prague Language Circle considered Bloomfield's phoneme to be the best presented and, for this reason, Trubetzkoy included it in the Circle's phonology treatise. Themes such as grammar and lexicology are worked on by Bloomfield in his works. With regard to phonemes and taxemes, Bloomfield defined them as grammatical arrangements arranged in various combinations and used daily by speakers in order to form the language and present the meaning of the word. The syntax and semantics present a logic admitted by the speakers of a speech community, in order to effect communication, both are arranged in the community and are recognized by its members, a foreigner would have difficulties in understanding them. Another relevant factor for understanding how the language happens and settles in the community supported by the cooperation of the speakers are the linguistic loans, which can be cultural, dialectal and intimate. They establish relations between different speech communities, establishing a linguistic exchange between them that can be both beneficial and harmful to the community. In part, the speaker is the one who assumes with his social group the responsibility to borrow a word, an expression or a sentence, however, on the other hand, when it comes to an intimate or intimidating loan, a community is seen as stronger at the expense of another that must, necessarily, assume the foreign language, is a demonstration of power. As for the concepts discussed by Leonard Bloomfield, in all of his works, there are four that lead all discussions started from the empirical observation and the method created by Bloomfield for the description of the language. Therefore, the concepts refer to language, an instrument that differentiates human beings, making them capable of transforming thinking into interpersonal communication. Phonemes reveal the identity of the speaker and the community, expose the subtleties of the language that are observable by the speakers themselves or by a linguist who has the intention of describing them. The speaking community is the social group cohesive and united by the language and similar phonemes produced by its members. A speech community has the mission to protect the spoken language, transmit it to the youngest members and preserve it so that its speakers are not lost in their own syntax, lexicon or semantics. Speakers are indoctrinated individuals to speak the language of the community, obey imposed rules and not distort the order of linguistic facts. They are the ones who make the language happen through speech, the identity of the community, however, they are not allowed to circumvent the rules of the community under penalty of being misinterpreted or misunderstood. Leonard Bloomfield's works focus on these pillars because it is substantial that every community has its own language constituted from peculiarities inherent to the speakers who use it. This thesis is based on the four concepts relevant to the understanding of the individual as part of a larger group capable of preserving their linguistic customs for the sake of maintaining the group's identity. Bloomfield was a pioneer in the recognition of the linguistic group, the speech community, an important factor for 20th century linguistics that can improve the concept and create new branches of linguistics. In short, it is here to enable the knowledge and recognition of Leonard Bloomfield as a precursor to a new linguistic method.